Development of Student Worksheets based Process Oriented Guided Inquiry Learning to Remediate Student’s Misconceptions on Acid and Base - Amalia Munjiatul Ummah; Harun Nasrudin (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to describe the feasibility of POGIL-based student worksheets to remediate misconceptions in terms of validity, practicality, and effectiveness, with the object of research of 11th grade students of Al-Islam Krian High School. Validity was measured from the content and construct validation sheets. The responses and activities of students measure practicality. Effectiveness is measured by the percentage of misconceptions that turn toward understanding the concept. The development of this Student Worksheet refers to the development of Research and Development (R&D). The model used is the 4D model, which consists of 4 stages, namely define, design, development, and dissemination. The research that has been carried out is limited to the development stage in the trial step. The validation result data is ordinal data that can be analyzed by determining the mode of each assessment aspect. The validity of worksheet is reviewed from the validity of content and construct which obtained a mode score of 4 with a valid category. The practicality results show that the worksheet is efficient with the activity for each trial of 95.56%, 95.56%; and 97.22%. The practicality of worksheet based on the POGIL learning model in terms of student response questionnaires using a Guttman scale through positive and negative statements with the answers "Yes" or "No" with the results of positive student responses of 95.78%.The effectiveness of the worksheet in terms of the results of shifting misconceptions towards understanding concepts was 81.06% in the theory of acids and bases, 70.09% in the strength of acids and bases, and 69.86% in acid and base indicators, with a significance value of 0.000 in the Wilcoxon test. The results showed that the POGIL-based worksheet developed was feasible to be able to remediate students' misconceptions on acid and base materials.